THE RELEVANCE OF MORAL EDUCATION IN SURAH LUQMAN VERSE 12-19 AS AN EFFORT TO MINIMIZE THE JUVENILE DELINQUENCY - Wulandari, Rika; Rosa Bustam, Betty Maulia (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
Juvenile delinquency is caused by developments and changing times, which impacts moral crises and promiscuity in adolescents and deviates from religious values. By applying the moral development contained in Luqman verses 12–19, efforts are urgently needed to minimize juvenile delinquency. This study aims to explain how the relevance of moral education in Surah Luqman verses 12–19 is an effort to minimize juvenile delinquency. Based on a literature study and descriptive-analytic method, the novelty in this study is the relevance of moral education in Luqman verses 12–19, which is very relevant to today's youth morals so that efforts to minimize juvenile delinquency according to child psychology depend on the character of the child and the background of the problem so that it is carried out by giving children a good understanding of religion, spending time with parents, giving positive advice to children, getting along with peers, and being able to control themselves well. By implementing these efforts, we can minimize juvenile delinquency today.